Epithelioid cell granuloma - Deepika Yadav; M Ramam (Wolters Kluwer Medknow Publications, 2018)
In this review, we use the term epithelioid cell granuloma for granulomas that show focal collections of epithelioid histiocytes in the absence of additional changes such as acute inflammatory cells and altered collagen or foreign material. Giant cells, lymphocytes, and histiocytes are often seen in these granulomas. Various features are useful in recognizing the specific cause of an epithelioid cell granuloma and include coalescence or discreteness of granulomas, presence and type of necrosis, inclusion bodies within giant cells, and identification of organisms, but the arrangement of granulomas within the dermis may be the single most important feature. Leprosy shows well-circumscribed, oval, oblong, and curvilinear epithelioid cell granulomas in a perivascular and peri-appendageal location involving superficial and deep dermis with minimal interstitial spill. Cutaneous tuberculosis is recognized by a lichenoid granulomatous pattern comprising a dense upper dermal infiltrate with granulomas that impinge on the overlying acanthotic epidermis accompanied by more localized, nodular granulomas in the deep dermis. Sarcoidosis has closely huddled yet discrete granulomas that have a paucity of lymphocytes. Other patterns and clues include follicular/perifollicular granulomas in lichen scrofulosorum and granulomatous rosacea, prominent necrosis in lupus miliaris disseminatus faciei, branching granulomas with plasma cells in granulomatous secondary syphilis, granulomatous lobular panniculitis with vasculitis in erythema induratum, messy granulomas in cutaneous leishmaniasis, and granulomas extending to the muscles in granulomatous cheilitis/Melkersson-Rosenthal syndrome. Histopathological findings, in combination with clinical and laboratory information, can lead to a specific diagnosis in the majority of cases.